2015
DOI: 10.1016/j.bpj.2014.11.1881
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Structure of a Calcium Activated TMEM16 Lipid Scramblase

Abstract: observation that synaptic strength correlates with dendritic spine morphology leads to the hypothesis that the mushroom-like shape of dendritic spines functions as a receptor trap. We developed a mimetic system to investigate dendritic spine morphology and its effects on receptor confinement and diffusion. Giant unilamellar vesicles (GUV's) are made from lipids using electroswelling. To mimic the mushroom-shaped morphologies of dendritic spines, a micromanipulator is used to pull membrane tubes from the GUV li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
200
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(212 citation statements)
references
References 0 publications
12
200
0
Order By: Relevance
“…can coordinate with Ca 2+ . Consistent with previous studies (Brunner et al, 2014;Tien et al, 2014;Yu et al, 2012), Dang et al (2017) found that the acidic residues E654, E702, E705, E734, and D738 group together to form two Ca 2+ -binding sites in TMEM16A. The present data have provided a framework to guide further studies of gating of CaCCs.…”
supporting
confidence: 91%
“…can coordinate with Ca 2+ . Consistent with previous studies (Brunner et al, 2014;Tien et al, 2014;Yu et al, 2012), Dang et al (2017) found that the acidic residues E654, E702, E705, E734, and D738 group together to form two Ca 2+ -binding sites in TMEM16A. The present data have provided a framework to guide further studies of gating of CaCCs.…”
supporting
confidence: 91%
“…23 Anoctamins can also function as phospholipid scramblases when activated by increases in calcium levels, whereby they promote cell death by moving phosphatidylserine from the inner to the outer leaflet of the plasma membrane. 24 Further, the expression of several members of F I G U R E 1 ANO3 rs74754887, ANO4 rs585335, ANO5 rs4622263, ANO7 rs62187431, and ANO10 rs118005571 are associated with biochemical recurrence (BCR)-free survival time. Values between brackets denote the number of patients F I G U R E 2 Functional analyses of candidate single-nucleotide polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…In a murine B-cell line model, the silencing of Ano6 resulted in an impairment of Ca 2+ -dependent PS exposure (12). A role of Anos as transporters for the negatively charged PS was also confirmed by structural analysis (14). In addition, there is substantial electrophysiological evidence that Ano6, like other members of the Ano family, can operate as aCa 2+ -induced ion channel that is permeable to chloride ions, monovalent cations, and calcium ions (10,(15)(16)(17).…”
mentioning
confidence: 85%